1976
DOI: 10.21273/jashs.101.4.394
|View full text |Cite
|
Sign up to set email alerts
|

Organic Acid Accumulation in Attached and Detached Tomato Fruits1

Abstract: Changes in acid content in fruits of tomato (Lycopersicon esculentum Mill.) left on the vine compared with those of fruits removed from the vine at one stage each of development and ripening. Developing fruits detached 28 days after anthesis had an increase in total acidity attributable to increased malic and citric acid concentrations. Detached developing fruits accumulated organic acids more rapidly than attached fruits. Mature fruits detached at the breaker stage decreased more in total acidity than attache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

1979
1979
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 15 publications
3
5
0
Order By: Relevance
“…The two-way interaction between drying methods and pre-drying treatment significantly (P ≤ 0.05) affected the TSS content of dried pumpkin fruit accessions (Table 2). Salted and fruit dried in the oven had the highest TSS content (9.2 ○ Brix) while the lowest TSS content (7.3 ○ Brix) was recorded in untreated (sun dried without pre-treatment) pumpkin fruit slices which is in agreement with the findings of several reports [23], [24] and [25]. [14] also reported that treating fruit and vegetables before drying saves lose of volatile compound and vitamins later during drying which could better explain the result of this study.…”
Section: Advanced Materials Research Vol 824supporting
confidence: 92%
See 2 more Smart Citations
“…The two-way interaction between drying methods and pre-drying treatment significantly (P ≤ 0.05) affected the TSS content of dried pumpkin fruit accessions (Table 2). Salted and fruit dried in the oven had the highest TSS content (9.2 ○ Brix) while the lowest TSS content (7.3 ○ Brix) was recorded in untreated (sun dried without pre-treatment) pumpkin fruit slices which is in agreement with the findings of several reports [23], [24] and [25]. [14] also reported that treating fruit and vegetables before drying saves lose of volatile compound and vitamins later during drying which could better explain the result of this study.…”
Section: Advanced Materials Research Vol 824supporting
confidence: 92%
“…Blanching is one of the most widely used pre-drying treatments in the dehydration procedures of most fruits and vegetables [16]. Research reports clearly showed that using appropriate drying conditions and pre-drying treatment significantly reduces the drying time of other fruit and vegetables [25] and [24].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…C itric and m alic acid concentrations changed at different rates during ripening, resulting in an increased citric : malic ratio with advanced ripening stage in both culti vars. This increase is consistent with pre vious reports for large-fruited cultivars (2,9). SF had a higher ratio than LRC at all stages, but the amount of difference was es pecially large in the table-ripe stage.…”
Section: Literature Citedsupporting
confidence: 92%
“…Organic acid accumulation in detached fruit is determined by metabolite levels at the time of detachment. Sakiyama and Stevens (18) found detached immature-green fruit to increase in titratable acidity at a higher rate than attached fruit.…”
Section: Resultsmentioning
confidence: 99%